PERAN ALAT MUSIK POLOPALO DALAM KEHIDUPAN SOSIAL DAN TRADISI MASYARAKAT GORONTALO: Alat musik popalo - Dimas Tri Purtanto; Muhammad Rizki As Sidiq; Sabrina Fidzah Kahlaa; Salsa Noviandani; Sulis Nur Adyanti; Syahirul Bahar; Farkhan Abdurochim Alfarauq (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The traditional Polopalo musical instrument is one of the cultural heritages of the Gorontalo people that serves more than just a medium of entertainment. This study aims to analyze the role of the Polopalo musical instrument in the social life and traditions of the Gorontalo people. The methods used are literature study and cultural observation to see how Polopalo is used in various social contexts, such as traditional ceremonies, art performances, and interactions between community members. The results of the analysis show that Polopalo plays a role as a medium of cultural expression, strengthening local identity, and strengthening social relations through shared activities such as playing folk music. In addition, Polopalo has historical and symbolic value that reflects the harmonious and communal character of the Gorontalo people. Thus, the existence of Polopalo is not only part of traditional art, but also an important element in maintaining social values ​​and traditions passed down from generation to generation.